Early Spatial Diffusion of Orchards in Himachal Pradesh; India (1950- 1995) - Kaur, Navneet (Indian Journal of Hill Farming, 2019)
Himachal Pradesh has condusive climate for the cultivation of fruits ranging from apple and stone fruits in the northern high hills to citrus and mango in lower hills. At present about 34 types of fruit species are grown in Himachal Pradesh on a bigger or smaller scale. Among these apple, pear, cherry, peach, plum, apricot, almond, walnut, pecan nut, mandarin, sweet orange, kagzi lime, hill lemon, mango, litchi, guava, kiwi fruit, olive, strawberry etc. are important. Apple is the most prominent fruit grown in Himachal Pradesh and occupies about49 percent of the total area under the fruits. All other fruits together account for the rest 51 percent. However the other fruits of Himachal have also contributed reasonably to the financial pool of the state hence there is a need to study these in detail. Diffusion of Apple orchards has already been highlighted by N. Kaur in her paper titled ‘Diffusion of apple orchards in Himachal Pradesh’ hence the present paper is an attempt to analyse the process of diffusion of other fruits in Himachal Pradesh which also hold an important place in the economy.